The determinants of housing price index in Malaysia: gross domestic product, population, inflation rate and unemployment rate / Nur Syafiqah Athirah M.Haizal - M.Haizal, Nur Syafiqah Athirah (Faculty of Business and Management, 2019)
The main purpose of this study is to measure the relationship between macroeconomic variables and the housing price index in Malaysia. This paper examines empirically whether the increasing trend in the Malaysian housing price is related to changes in the gross domestic product (GDP), population, inflations rate, and unemployment rate. The paper is exploratory in nature. The empirical data were collected from Valuation and Property Services Department of the Ministry of Finance Malaysia and World Bank Data from 1988 to 2018. The paper provides empirical results that all the macroeconomics variables are the key determinants of housing prices. However, changes in housing prices may not necessarily be influenced by all the macroeconomic variables in Malaysia. The general finding of this paper strongly suggests that housing bubbles in the Malaysian residential property market are becoming bigger and stronger. The paper is useful for house developer, future researcher and policy maker to know which factors to account for in housing investment decision. This paper can serve as a guide for the government in stabilizing the residential housing price in Malaysia.